Question
Multiply. \[ (a-3)(a+3) \] Simplify your answer. \( \square \)
Ask by Boyd Horton. in the United States
Feb 03,2025
Real Tutor Solution
Tutor-Verified Answer
Answer
\( a^2 - 9 \)
Solution
Sign in to Unlock Answers for Free!
A Learning Platform Trusted by Millions of Real Students and Teachers.
Unlock
Reviewed and approved by the UpStudy tutoring team
Like
Extra Insights
To simplify \( (a-3)(a+3) \), you can use the difference of squares formula, which states that \( (x-y)(x+y) = x^2 - y^2 \). Here, \( x = a \) and \( y = 3 \). So, applying the formula, we get: \[ (a-3)(a+3) = a^2 - 3^2 = a^2 - 9. \] Thus, the simplified result is: \[ a^2 - 9. \]